Fatty pancreas: A possible risk factor for pancreatic cancer in animals and humans. Issue 10 (5th September 2018) - Takahashi, Mami; Hori, Mika; Ishigamori, Rikako; Mutoh, Michihiro; Imai, Toshio; Nakagama, Hitoshi
Abstract : Obesity, type 2 diabetes mellitus (T2DM) and aging are associated with pancreatic cancer risk, but the mechanisms of pancreatic cancer development caused by these factors are not clearly understood. Syrian golden hamsters are susceptible to N ‐nitroso bis (2‐oxopropyl)amine (BOP)‐induced pancreatic carcinogenesis. Aging, BOP treatment and/or a high‐fat diet cause severe and scattered fatty infiltration (FI) of the pancreas with abnormal adipokine production and promote pancreatic ductal adenocarcinoma (PDAC) development. The KK‐ A y mouse, a T2DM model, also develops severe and scattered FI of the pancreas. Treatment with BOP induced significantly higher cell proliferation in the pancreatic ducts of KK‐ A y mice, but not in those of ICR and C57BL/6J mice, both of which are characterized by an absence of scattered FI. Thus, we hypothesized that severely scattered FI may be involved in the susceptibility to PDAC development. Indeed, severe pancreatic FI, or fatty pancreas, is observed in humans and is associated with age, body mass index (BMI) and DM, which are risk factors for pancreatic cancer. We analyzed the degree of FI in the non‐cancerous parts of PDAC and non‐PDAC patients who had undergone pancreatoduodenectomy by histopathology and demonstrated that the degree of pancreatic FI in PDAC cases is significantly higher than that in non‐PDAC controls. Moreover, the association with PDAC is positive, even after adjusting for BMI and the prevalence of DM. Accumulating evidence suggests that pancreatic FI is involved in PDAC development in animals and humans, and further investigations to clarify the genetic and environmental factors that cause pancreatic FI are warranted. Abstract : Fatty infiltration (FI) of the pancreas is observed in humans and associated with age, obesity and type 2 diabetes, and is suggested to be a possible risk factor for pancreatic cancer. Observation of the pancreas of experimental animals showed that there is species/strain difference in susceptibility to developing intralobular scattered pancreatic FI, suggesting a contribution of genetic factors, and this may be related to pancreatic cancer susceptibility.